Inverted L‐notch loaded hexa band circular patch antenna for X, ku/K band applications. Issue 8 (15th June 2018) - Singh, Vivek; Mishra, Brijesh; Dwivedi, Ajay Kumar; Singh, Rajeev
Abstract: A novel hexa band circular shape patch antenna with four inverted L‐shape notches is proposed. The antenna results are discussed in terms of reflection coefficient, surface current density, radiation pattern (co and cross polarization), three‐dimensional gain distribution, and voltage standing wave ratio (VSWR). Measured resonating frequencies are observed at 11.6, 13.92, 17.11, 19.47, 21.11, and 23.05 GHz. Simulated gain of 7.39 dBi (11 GHz), 2.25 dBi (13.3 GHz), 6.65 dBi (16.6 GHz), 5.83 dBi (19 GHz), 6.02 dBi (20.6 GHz), and 7.31 dBi (22.2 GHz), respectively, is observed and the antenna is suitable for X‐band, Ku‐band, and K‐band applications. The performance of the proposed antenna is validated in terms of return loss (dB), VSWR, and radiation pattern by measurement.